The role of human heart-type Fatty Acid Binding Protein in the early detection of myocardial injury in Acute Coronary Syndrome - Zahid Mehmood, Zahid Mehmood; Tariq Feroze Khawaja, Tariq Feroze Khawaja (Journal of Rawalpindi Medical College, 2020)
Objectives: To evaluate the use of H-FABP as a novel marker in early detection of cardiac damage (MI) in patients presenting with symptoms of the acute coronary syndrome (ACS). Methods: This cross-sectional study included 250 subjects; 125 patients of ACS presenting within four hours of the onset of chest pain and/dyspnea and 125 age and sex-matched healthy controls. An initial blood sample was taken from patients at presentation. Blood samples of healthy control subjects were also taken. The blood samples of both groups were centrifuged and stored at -200 C for H-FABP analysis. All the patients and control subjects were thoroughly examined and detailed history was taken. The diagnostic test was troponin-T.H-FABP concentrations of all samples were measured by ELISA-kit. The results were analyzed statistically. A p-value≤0.05 was considered statistically significant. Results: In 125 patients of ACS, H-FABP showed a sensitivity of 85% and specificity of 83.3% for acute MI diagnosis at a cut-off level of 16 ng/ml. Positive predictive values and negative predictive values were 96.8% and 48.4% respectively. The accuracy was 84.4%and the area under the ROC curve was 0.842. Conclusion: Evaluation of heart-type fatty acid-binding Protein (H-FABP) within four hours of onset ACS symptoms may be a valuable tool in the diagnosis of AMI.